PENGOLAHAN KAYU & BESI BEKAS SEBAGAI WADAH MENGURAI MANGGARAI DALAM PENYELESAIAN WAJAH KAWASAN MELALUI URBAN AKUPUNKTUR - Mega Widiya; Sutarki Sutisna (Jurusan Arsitektur dan Perencanaan, 2022)
Every district continues to move forward in response to the increasingly diverse community activities in the city’s rapid development. Manggarai is one of the old and complex districts in South Jakarta that holds various historical values and problems. Growing up with its initial face as a commercial area, the development has shifted Manggarai into a transit-oriented area as its new face. Local people complain that movement is limited to arterial roads causing some areas to stagnate and degrade due to the lack of attractors. Therefore, this project seeks to regenerate community expectations regarding the realization of potential and memory through urban acupuncture methods. With this idea, “unraveling spot” is built by dissecting the urban context using the image of the city theory, which describes various issues and potentials that can be raised as targets in answering the value of urban acupuncture itself. The analysis will lead to the design of the used goods business in the wood and iron sector that is still existing and is in demand by the public which later will have programs such as gallery, hangout space, cultural stage, market, and culinary area, as well as green open space. In conclusion, this project aims to strengthen community interaction and participation, which will lead to an even distribution of movement, the emergence of community, equality, and recreational nodes network. Keywords: Community Empowerment; Image of the City; Recreation; Scrap Wooden Metal; Urban Acupuncture Abstrak Berbagai kawasan terus bergerak maju guna merespon semakin beragamnya aktivitas masyarakat dalam pesatnya perkembangan kota. Manggarai menjadi salah satu kawasan tua dan kompleks di Jakarta Selatan yang menyimpan beragam nilai historis dan persoalan. Tumbuh dengan wajah awalnya sebagai kawasan perniagaan namun perkembangan membawanya beralih menjadi kawasan berorientasi transit sebagai wajah barunya. Masyarakat setempat mengeluhkan pergerakan yang sebatas pada jalan-jalan arteri menyebabkan beberapa area stagnan dan berdegradasi karena kurangnya atraktor pada kawasan. Oleh karena itu, proyek ini berusaha menumbuhkan kembali harapan masyarakat mengenai pengangkatan kembali potensi dan memori kawasan melalui metode akupunktur perkotaan. Dengan gagasan ini, “wadah mengurai” dibangun dengan membedah konteks perkotaan menggunakan teori citra kota yang menjabarkan berbagai isu dan potensi yang diangkat sebagai sasaran dalam penerapan akupunktur perkotaan itu sendiri. Analisis tersebut akan berujung pada perancangan bisnis barang bekas di sektor kayu dan besi yang masih memiliki eksistensi dan diminati masyarakat dimana nantinya program seperti galeri, tempat nongkrong, panggung budaya, wadah jual beli, dan area kuliner, serta ruang terbuka hijau. Kesimpulannya, proyek ini bertujuan untuk mempererat interaksi dan partisipasi masyarakat yang akan membawa penyebaran perpindahan yang merata, timbulnya komunitas, kesetaraan, dan jaringan simpul rekreasi yang utuh.